An effective clean energy transition must anticipate growing climate disruptions. (7th July 2022) - Lesk, Corey; Kornhuber, Kai
Abstract: As the clean energy transition gathers momentum, it will face myriad technical, economic, and political challenges. However, one in particular is often underappreciated: the potential disruption to the transition from surging climate extremes. We identify three ways in which extreme events may impede the transition: direct physical impacts to transitional infrastructure, strained resources due to rising recovery costs, and political backlash from disaster-affected populations. If these pitfalls materialize, the transition could stall, leading to continued emissions, additional worsening of climate extremes, and further disruption of the transition. We propose three avenues to avoid this potential positive feedback: integration of adaptation and mitigation as mutually supportive goals, fostering political and cultural commitment to a sustained transition, and an interdisciplinary research and training agenda to improve modeling and preparedness for the cascading impacts of climate extremes